Pengaruh Desain Interior Perpustakaan Terhadap Minat Berkunjung di Dinas Kearsipan dan Perpustakaan Kabupaten Timor Tengah Selatan - Yunvrid Imanuel Taneofeto; Anton Hermawan; Elizabeth Sri Lestari (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
One of the government's efforts to educate the public is through public libraries in the regions. In fact, there is still low interest in visiting the local public library. The low interest in visiting certainly needs to get attention from the government seeing the important role of the library in increasing people's intelligence. One of the solutions to increase visitor interest is to pay attention to the interior design of the library. Therefore researchers are interested in conducting research related to this. This research is important to do to understand how much influence the interior design of the library has on the visitor's interest in visiting. This research method is quantitative research. Data collection techniques using interviews and questionnaires. Sampling was carried out randomly to all users in the regional library of South Central Timor Regency with a total of 75 people using a regression study. Presentation of research results in the form of research results tables and interpretation of test results. Testing the research results using the help of the SPSS version 22.0 program. with the results of the final hypothesis testing, the results obtained are t count>t table, namely 8.441> 1.665. The results of this study state that the interior design of the regional library of South Central Timor Regency has a significant effect on the public's interest in visiting. Based on the results of the research, it is necessary to have a good and mature interior design from the government, in this case the regional library, to increase interest in visiting the community. Keywords: Design interior; Interest Visit; Regional Library.